NOTCH4 mutation as predictive biomarker for immunotherapy benefits in NRAS wildtype melanoma - Li, Hongxia; Zhang, Qin; Duan, Qianqian; Tan, Yuan; Sun, Tingting; Qi, Chuang (Frontiers in Immunology, 2022)
Background NRAS wildtype melanoma accounts for approximately 80% of melanomas. Previous studies have shown that NRAS wildtype melanoma had higher response rates and better prognoses than NRAS-mutant patients following immunotherapy, while as major actors in tumor cells and tumor microenvironment (TME), the association between NOTCH family genes and response to immunotherapy in NRAS wildtype melanoma remains indistinct. Objective We aim to explore whether NOTCH family gene variation is associated with genomic factors in immune checkpoint inhibitor (ICI) response in NRAS wildtype melanoma and with clinical results in these patients. Method This research used genomic data of 265 NRAS wildtype ICI-pretreatment samples from five ICI-treated melanoma cohorts to analyze the relationship between NOTCH family gene mutation and the efficacy of ICI therapy. Results NRAS wildtype melanomas with NOTCH4-Mut were identified to be associated with prolonged overall survival (OS) in both the discovery (HR: 0.30, 95% CI: 0.11–0.83, P = 0.01) and validation cohorts(HR: 0.21, 95% CI: 0.07–0.68, P = 0.003). Moreover, NOTCH4-Mut melanoma had a superior clinical response in the discovery cohort (ORR, 40.0% vs 13.11%, P = 0.057) and validation cohort (ORR, 68.75% vs 30.07%, P = 0.004). Further exploration found that NOTCH4-Mut tumors had higher tumor mutation burden (TMB) and tumor neoantigen burden (TNB) (P <0.05). NOTCH4-Mut tumors had a significantly increased mutation in the DNA damage response (DDR) pathway. Gene set enrichment analysis revealed NOTCH4-Mut tumor enhanced anti-tumor immunity. Conclusion NOTCH4 mutation may promote tumor immunity and serve as a biomarker to predict good immune response in NRAS wildtype melanoma and guide immunotherapeutic responsiveness.